EVALUATION OF ANTINOCICEPTIVE AND ANTIPYRETIC ACTIVITIES OF SALIX TETRASPERMA ROXBURG - J.H.VIRUPAKSHA,; RAMA RAO NADENDLA,; M.SATISHKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
The present study was designed to evaluate antinociceptive and antipyretic activities of leaf extracts of Salix tetrasperma Roxburgh in rodents. The ethanolic and aqueous leaf extracts were tested for antinociceptive and antipyretic activities. Antinociceptive activity was evaluated using thremoceptive models namely eddy’s Hot plate and tail flick by analgesiometer. The antipyretic activity was evaluated using brewer’s yeast induced method. Retreatment with ethanolic and aqueous extracts of Salix tetrasperma leaves at 200 and 400 mg/kg showed significant dose dependent antinociceptive activity in the tested models. Both the extracts lowered the elevated rectal temperature in the brewer’s yeast induced pyretic model in a dose dependent manner. The findings in this study suggest that the ethanolic and aqueous leaf extracts of Salix tetrasperma possesses antinociceptive and antipyretic activity. Thus it provides a scientific evidence for its traditional claim.